(untitled) (Journal of Humanitarian and Applied Sciences, 2026)
The Libyan public construction sector faces multiple challenges in successfully implementing projects, among which contractor selection represents a critical factor. This study aims to evaluate the contractor’s role in construction project failure in order to identify the key criteria that should be considered when selecting contractors. To achieve the objectives of the study, data were collected through questionnaires distributed to a group of academic and non-academic experts working in the Libyan construction sector. The study adopted a descriptive-analytical approach. The findings revealed that the contractor’s influence on construction project failure in the Libyan public sector is ranked as the most significant factor, with a moderate to high level of impact. Moreover, the results identified the most important contractor selection criteria, including site management and supervision, financial ethics (avoiding bribery), project team competence, credibility and avoidance of personal or tribal bias, construction methods, planning management, availability of machinery and equipment, prior experience, financial stability, and financial management.